Edukasi Terapi Rendam Kaki dengan Garam dan Aromaterapi di PMB Muzilatul Nisma Kota Jambi - Selpyani Sinulingga; Sirly Patriani (Jurnal Abdimas Kesehatan (JAK), 2023)
Foot bath with warm water is one of hydrotherapy that uses warm water as a therapeutic agent for various health problems and has a physiological impact on the body. Physical and psychological changes in pregnant women can cause discomfort or complaints starting from the first trimester to the third trimester. The use of foot bath therapy with salt and aromatherapy will help pregnant women to get benefits such as lowering blood pressure, increasing circulation, reducing edema, increasing muscle relaxation. , increase comfort against of pain, reduce muscle spasm, increase and maintain endurance. The purpose of this activity is to increase the knowledge and skills of pregnant women about the use of Foot bath Therapy with Salt and Aromatherapy in pregnancy. The target of this activity is carried out on pregnant women in the second and third trimesters. the activity is start from pre-test implementation, providing education by giving leaflets, demonstration of Foot bath Therapy with Salt and Aromatherapy and post-test implementation. The results explain that there is an increase in knowledge of 41.25%. With this educational activity, it is hoped that there is increase in comfort and reduction of pain to the woman during pregnancy will be achieved and to support the realization of a safe and comfortable pregnancy.